PENGARUH PELAKSANAAN PROMOSI DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PLAZA MEBEL FURNITURE CENTER PEKANBARU - Azura, Mardian; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study was conducted at Plaza Mebel Furniture Center Pekanbaru which is located on Soekarno Hatta No.89A, Tangkerang Barat, Pekanbaru City, Riau, 28282. This study aims to determine the effect of promotion and pricing decision on purchasing at the Furniture Center Plaza Pekanbaru. Data analysis using descriptive analysis by using SPSS Program. The population was 7.200 Furniture Center Plaza Pekanbaru buyers in the five last years and samples were taken were 100 respondents. and techniques used Accidental sampling. Hypothesis testing uses a simple linear analysis method and multiple linear analysis with the results showing that the effect of promotion and pricing has a significant effect on purchasing decisions at the Furniture Center Plaza Pekanbaru. With a simple calculation of the coefficient of determination (R2) the implementation of promotion on purchasing decisions obtained by the value of R Square of 0.404 or 40.4% and the pricing of purchasing decisions obtained R Square value of 0.453 or 45.3% and multiple determination calculations (R2) of promotion and pricing for purchasing decisions obtained R Square value of 0.528 or 52.8%. This shows that the effect of promotion and pricing has an effect of 52.8% on purchasing decisions at the Furniture Center Plaza Pekanbaru, while the remaining 47.2% is influenced by other variables not examined in this study. Keywords: Promotion, Pricing, Purchasing Decisions